MANAJEMEN KEPALA SEKOLAH DALAM MENGATASI DEGRADASI MORAL PESERTA DIDIK SMAN 13 BONE - RISNAWATI, RISNAWATI; AMRI, MUH.; BAHARUDDIN, BAHARUDDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Principal management in education is very necessary, especially in moral development. Morals are self-awareness that arises from the deepest inner self to follow and obey the rules, values ??and laws that apply in a particular environment. Morals are also a means of education. In educating morals, the role of influencing, encouraging, controlling, changing, forming certain morals is in accordance with the values ??that are instilled, taught and exemplified. Changes in a person's morals, including their achievements, are the result of planned education and learning. This research was conducted at SMAN 13 Bone and the aim of the research was planning, organizing, implementing and supervising in overcoming the moral degradation of students at SMAN 13 Bone. The results of this research show that the planning (Planning) of the school principal's management in overcoming the moral degradation of students is carried out by planning activities to instill character education both in the family environment, educational institutions and has been implemented and monitored by the principal, organizing the principal's management in overcoming degradation. The morale of students has been implemented by dividing their respective tasks and collaborating with stakeholders, implementing (actuating) the school principal's management in overcoming the moral degradation of students by carrying out all activities so that there are no students who violate the school's code of ethics, supervising (controlling) management school principals in overcoming the moral degradation of students through visible monitoring of the progress of all activities as desired. ABSTRAKManajemen Kepala sekolah dalam pendidikan, sangat diperlukan khususnya dalam pembinaan moral. Moral merupakan kesadaran diri yang muncul dari batin terdalam untuk mengikti dan menaati peraturan-peraturan, nilai-nilai dan hukum yang berlaku dalam suatu lingkungan tertentu. Moral juga menjadi sarana pendidikan. Dalam mendidik moral berperan memengaruhi, mendorong, mengendalikan, mengubah, membentuk moral tertentu sesuai dengan nilai-nilai yang ditanamkan, diajarkan, dan diteladankan. Perubahan moral seseorang termasuk prestasinya hasil dari suatu pendidikan dan pembelajaran terencana. Penelitian ini dilakukan di SMAN 13 Bone dan tujuan penelitiannya adalah perencaan pengorganisasian pelaksanaan dan pengawasan dalam mengatasi degradasi moral peserta didik SMAN 13 Bone. Hasil penelitian ini menunjukkan bahwa perencanaan (Planning) manajemen kepala sekolah dalam mengatasi degradasi moral peserta didik dilakukan dengan perencanaaan kegiatan menanamkan pendidikan karakter baik lingkungan keluarga, instansi pendidikan dan sudah diimplementasikan serta dimonitor oleh kepala sekolah, pengorganisasian (organizing) manajemen kepala sekolah dalam mengatasi degradasi moral peserta didik sudah terlaksana dengan cara melakukan pembagian tugas masing-masing dan kerjasama dengan stakeholder, pelaksaan (actuating) manajemen kepala sekolah dalam mengatasi degradasi moral peserta didik dengan terlaksananya semua kegiatan sehingga jaranya peserta didik yang melanggar kode etik sekolah, pengawasan (controling) manajemen kepala sekolah dalam mengatasi degradasi moral peserta didik dengan melalui pemantauan yang terlihat dari berjalanya semua kegiatan sesuai yang diinginkan.